Creating an image in real estate advertising texts - Dmitry S. Sknarev (RUDN Journal of Studies in Literature and Journalism, 2020)
This article presents some results obtained in the study of the advertising image characteristics in marketing communications (on the example of Russian residential real estate advertising). The study materials present print media advertising and online advertising, as well as construction companies and residential areas websites. To achieve the goal, a survey, analytical, theoretical, systemic, pragmatic methods, as well as methods of continuous sampling of linguistic means, techniques and units from marketing communications texts that create an image of a product, and of semantic interpretation and identification were used. The analysis revealed that brand names, epithets, metaphors and phraseological units are the most productive in creating the image of residential real estate in marketing communications. The concept of social and ethical marketing integrates advertising of real estate marketing products, when the product image goes beyond consumption standards and becomes media itself, creating a new communication.